Revitalizing education: unveiling Allama Muhammad Iqbal’s vision for empowering the Muslim ummah - Hussien, Suhailah; Lone, Ajaz Ahmad (International Journal of Science and Research (IJSR), 2023)
The revolutionary philosopher Allama Muhammad Iqbal enlightens and encourages the whole Muslim Ummah in general and the Muslims of the Subcontinent specially. Despite being a philosopher and poet, Dr. Mohammad Allama Iqbal addressed the root causes of the issues that plagued Muslim countries by considering and advocating for improvements of the educational system. He believed that reformation & transformation could be done by fostering self-awareness, advancing education, and distributing information. This article aims to clarify the education strategy that results from Iqbal's conception of education. The objectives of the study are: to investigate the views of Iqbal about Educational thoughts; to search out the main purpose of education and design curriculum in the light of Iqbal's Educational thoughts; to explore Suggested Teaching Methodology and the role of an ideal Teacher in Iqbal Philosophy. Qualitative research method is used for the study. Findings of the study showed that Muhammad Iqbal’s educational thoughts indicate holistic approach of nurturing an individual. His study focused on reviving the spirit of intellectualism in academics. Inculcation of spirituality in education system, based on Islamic ideology is the ultimate aim of education. The effect of this aim will be reflected in curriculum design, teaching methodology and personality of the teacher. Muhammad Iqbal's initiative is still applicable today, because education has a worldwide impact on daily life, forming devout believers or people who are seen to be well-advanced.